Enhanced sodium-ion storage of nitrogen-rich hard carbon by NaCl intercalation. (October 2017) - Hu, Mingxiang; Yang, Le; Zhou, Kai; Zhou, Chengshuang; Huang, Zheng-Hong; Kang, Feiyu; Lv, Ruitao
Abstract: The sodium-ion battery (SIB) has been considered as one of the most important and promising candidates for large-scale storage of electrical energy. Developing cost-effective but high-performance anode materials is crucial for SIBs. Herein a hard carbon-based anode material is synthesized from polyurethane foam. In order to boost its performance, NaCl, one of the most abundant and low-cost salts in the ocean, is used to intercalate hard carbon. To the best of our knowledge, reports on NaCl intercalation in sodium ion battery anode materials are very scarce so far. After Na + intercalation, the as-obtained sample delivers a capacity of over 210 mAh g −1 at 20 mA g −1 . Moreover, a 90 mAh g −1 specific capacity with over 78% retention can be achieved after 1000 cycles at 1 A g −1 current density, which is 100% higher than that of untreated samples. The much enhanced performance can be attributed to a synergetic effect of both heteroatom doping and Na + intercalation which can improve the electronic/ionic conductivity and enlarge the lattice spacing of the hard carbon as well. This work demonstrates that NaCl-intercalated nitrogen-rich hard carbons are very promising in their ability to serve as a kind of low-cost but efficient anode material for SIBs. Graphical abstract: